THE REVIVAL OF NATIONAL VALUES, CULTURE, AND TRADITIONS IN A POST-INDEPENDENCE SOCIETY OF UZBEKISTAN (International journal of artificial intelligence, 2024)
Following the collapse of the Soviet Union and the subsequent independence of Uzbekistan in 1991, a profound transformation took place in the country’s social, cultural, and political realms. Central to this transformation has been the revival of national values, culture, and traditions long overshadowed by decades of Soviet dominance. This article examines the factors contributing to this cultural resurgence, exploring how renewed emphasis on language, heritage, and spiritual identity has informed nation-building and social cohesion. The study draws on literature, policy documents, and comparative analyses to highlight the ongoing interplay between historical memory, modern statehood, and globalization. The findings suggest that while the revival of national values fosters a stronger sense of identity and unity, it must also navigate contemporary challenges, including balancing tradition with progressive reform, addressing external cultural influences, and ensuring inclusivity in cultural policies.